Formação da Comunidade Folio no Brasil - (:unkn) unknown (Associação Nacional de Pesquisa e Pós-Graduação em Ciência da Informação, 2019)
New technologies emerge every day and contribute to the evolution of libraries in order to extrapolate their physical manifestation, both by operating hours and geographical reach. The open source platform FOLIO presents a new model for library management, through a web service that allows the choice of relevant applications and services for each library. Thus, this study has an exploratory aspect and uses documentary research to collect documents about the formation of the FOLIO community in Brazil. Meetings, lectures, blog posts and interviews were collected to create a track record about the platform in Brazil.
Formation of the Folio Community in Brazil
Keywords: Software livre; Sistemas integrados de automação de bibliotecas; Automação de bibliotecas; Comunidades; Biblioteconomia